Revisiting representative form in ISIS media: How emerging collectives reconstitute communities in the 21st century - Winkler, Carol K. (Frontiers in Communication, 2022)
This study reconsiders the concepts of representative form and visual ideographs in the context of collectives-in-formation heavily reliant on the online environment to communicate with global audiences. Focusing on the online media products of ISIS, the study conducts a quantitative content analysis of over 9,000 images that the group distributed from 2014 to 2020, coupled with a qualitative assessment of the group's religious and institutional contexts. The findings add to current understandings of how reconstituted communities develop visual ideographs by showing how predictable constellations of iconic and non-iconic compositional elements combine to create representative forms and how non-parodied images can also function as ideographs. The study also documents that ISIS uses differential language-based targeting strategies for visual ideographs and demonstrates how institutional definitions can serve as critical intervening variables for understanding the reinforcing relationship that can exist between icons and verbal ideographs.